Results of pulsed radiofrequency technique with two laterally placed electrodes in the annulus in patients with chronic lumbar discogenic pain - Fukui, Sei; Rohof, Olav (Journal of anesthesia, 2012)
Discogenic pain is an important cause of low back pain (LBP). We have developed a pulsed radiofrequency (P-RF) technique, using two electrodes placed bilaterally in the annulus, for applying radiofrequency current in the disc (bi-annular P-RF disc method). The purpose of this study was to investigate the effect of the bi-annular P-RF disc method, using Diskit needles (Neurotherm, Middleton, MA, USA) in patients with discogenic LBP. The subjects were 15 patients with a mean age of 37.3 ± 8.63 years with chronic discogenic lower back pain that was not responsive to aggressive nonoperative care. Two Diskit II needles (15-cm length, 20G needles with a 20-mm active tip) were placed bilaterally in the annulus in the disc. Pulsed radiofrequency was applied for 12 min at a setting of 5 × 50 ms/s and 60 V. The pain intensity scores on a 0–10 numeric rating scale (NRS) and the Roland–Morris Disability Questionnaire (RMDQ) were measured pretreatment, and at 1 week and 1, 3, and 6 months post-treatment. The mean pain severity score (NRS) improved from 7.27 ± 0.58 pretreatment to 2.5 ± 0.94 at the 6-month follow-up ( p < 0.01). The RMDQ showed significant ( p < 0.01) improvement, from 10.70 ± 2.35 pretreatment to 2.10 ± 1.85 at the 6-month follow up ( p < 0.01). The bi-annular P-RF disc method with consecutive P-RF 5/5/60 V, 12-min (with Diskit needle), appears to be a safe, minimally invasive treatment option for patients with chronic discogenic LBP.